Interdependence of temperature and land use on water quality in urban lakes, Vellore, Tamil Nadu, India - Manjunath, D. R.; Jagadeesh, P. (Frontiers in Water, 2025)
Urban lakes provide crucial ecological, social, and economic benefits, but rapid urbanization and land use changes have significantly compromised their health and sustainability. This study investigates the interrelations among land use, temperature, and water quality in Vellore lakes (1997–2024) to address the sustainable development goals (SDG) 6.4 (water) and 13.3 (climate resilience). Satellite derived data revealed a direct correlation between a reduced water spread area (1.82%) and increasing LSTs, underscoring the adverse effects of urbanization. Notably, 64% of dissolved oxygen (DO) of the samples surpassed permissible limits. Hardness, electrical conductivity (EC), total dissolved solids (TDS) and DO emerge as the primary influencers of the Water Quality Index (WQI). It was validated by the XGBoost model. Based on WQI most of the lake water classified as “Poor” for drinking. Principle component analysis revealed 68% of the variance in water quality with main factors as LST, built-up, and vegetative cover. Furthermore, suggesting that implementing 30% green buffers, restoring 2–5% WSA, and adopting climate-smart urban planning could lower LST by 1.8°C. These science-driven strategies align with the SDGs and India’s Smart Cities Mission, offering a pathway to harmonize urbanization with ecological resilience and safeguard lake biodiversity under a changing climate.